2015
DOI: 10.2166/wpt.2015.013
|View full text |Cite
|
Sign up to set email alerts
|

Performance of constructed wetlands with ornamental plants in the treatment of domestic wastewater under the tropical climate of South Mexico

Abstract: In developing countries located in tropical and subtropical regions, the use of ornamental plant species in constructed wetlands (CWs) could add benefits to the treatment of wastewater. This paper presents a study on the efficiency of using plants of economic importance in South Mexico (Heliconia stricta, Heliconia psittacorum and Alpinia purpurata) within an anaerobic digester horizontal subsurface CW system for treating domestic wastewater. The CW with H. psittacorum showed the highest level of removal of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 35 publications
1
3
0
1
Order By: Relevance
“…In relation to the total dissolved solids (TDS), these mainly include organic salts and residues, therefore, in terms of their decrease in treatment systems it becomes an indicator of their effectiveness [26]. In this study, a significant decrease of TDS was found (p > 0.05) in relation to the value of the influent (Table 1), these values found, after treatment in CWs, are within the limits allowed by the United States Environmental Protection Agency [27] which indicates that 500 mg L −1 is a suitable range for discharges to surface bodies and are consistent with those reported by other studies in similar conditions using CWs, where reduced values have been found after treatment in these systems [28].…”
Section: Control Parameterssupporting
confidence: 90%
“…In relation to the total dissolved solids (TDS), these mainly include organic salts and residues, therefore, in terms of their decrease in treatment systems it becomes an indicator of their effectiveness [26]. In this study, a significant decrease of TDS was found (p > 0.05) in relation to the value of the influent (Table 1), these values found, after treatment in CWs, are within the limits allowed by the United States Environmental Protection Agency [27] which indicates that 500 mg L −1 is a suitable range for discharges to surface bodies and are consistent with those reported by other studies in similar conditions using CWs, where reduced values have been found after treatment in these systems [28].…”
Section: Control Parameterssupporting
confidence: 90%
“…Los autores del estudio mencionan que con el CW en H. psittacorum se mostró el nivel más alto de remoción de demanda bioquímica de oxígeno (48%), demanda química de oxígeno (64%), fósforo total (39%) y nitrógeno total (39%). Esta especie y H. stricta pueden ser una alternativa viable al uso macrófitas en CW en áreas tropicales como Chiapas (Méndez-Mendoza et al, 2015).…”
Section: Heliconias Y El Uso Del Aguaunclassified
“…As one of the types of CW, horizontal subsurface constructed wetlands, have been applied in a wide range of wastewater treatments, especially for domestic wastewater ( Vymazal, 2009 ; Hua et al., 2017 ). Ornamental plants have also been used in some CWs due to their aesthetics and good removal efficiency ( Konnerup et al., 2009 ; Calheiros et al., 2015 ; Méndez-Mendoza et al., 2015 ). Plants provide the need for degrading microbes such as carbon, and habitat for microbes (zones of roots, stems and leaves) that are submerged in wastewater ( Brix, 2003 ).…”
Section: Introductionmentioning
confidence: 99%
“…CWs have been studied at a number of different scales. Higher removal efficiency has been shown in laboratory-scale CW compared to full-scale CW since plants often show better removal efficiency at a smaller scale and in controlled environments ( Méndez-Mendoza et al., 2015 ). Full-scale CWs have the advantage of providing real world results in comparison to implementation at micro or meso scales ( Brisson and Chazarenc, 2009 ) and several studies have demonstrated full-scale CWs can achieve more than 60% removal efficiency ( Sim et al., 2008 ; Vystavna et al., 2017 ; Ali et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation